Aclaramiento dental y su efecto en las estructuras del diente, según revisión sistemática de la literatura (2022)
The use of dental whitening in recent decades has been booming, therefore, it is essential to describe the effects that whitening agents can generate, such as hydrogen peroxide and carbamide peroxide with office technique and technique in House.